Study the Effect of Carbon Fiber Volume Fraction and their Orientations on the Thermal Conductivity of the Polymer Composite Materials. - Hamza, Mohammed Sellab (Al-Khwarizmi Engineering Journal, 2008)
The effect of fiber volume fraction of the carbon fiber on the thermal conductivity of the polymer composite material was studied. Different percentages of carbon fibers were used (5%, 10%, 15%, 20%, and 25%). Specimens were made in two groups for unsaturated polyester as a matrix and carbon fibers, first group has parallel arrangement of fibers and the second group has perpendicular arrangement of fibers on the thermal flow, Lee’s disk method was used for testing the specimens. This study showed that the values of the of thermal conductivity of the specimens when the fibers arranged in parallel direction was higher than that when the fibers arranged in the perpendicular direction The results indicated that the thermal conductivity increases with the increasing the fiber volume fraction. Minimum value was (0.64 W/m.°C) for parallel arrangement and (0.1715 W/m.°C) for perpendicular arrangement at (Vf = 5%) .Maximum value for parallel and perpendicular were (2.65 W/m. °C) and (0.215 W/m.°C) at (Vf = 25%) respectively.